Optimalisasi MPPT Photovoltaic Seri-Paralel dengan Kondisi Berbayang - Pambudi, Wahyu Setyo; Kurniawan, Haris; Uman Putra, Novian Patria; Munir, Misbahul; Fahruzi, Akhmad (Institut Teknologi Adhi Tama Surabaya, 2025)
Renewable energy sources are becoming increasingly essential to meet global energy demands, given the depletion of fossil fuel reserves. Solar energy, mainly through photovoltaic (PV) technology, provides a viable solution by converting solar radiation into electricity. Photovoltaic systems, composed of multiple panels connected in series and parallel, depend on factors such as radiation intensity and temperature. Maximum Power Point Tracking (MPPT) commonly can optimize power output, but conventional methods often struggle in partial shading conditions, leading to local peak trapping. This research combined Particle Swarm Optimization (PSO) with MPPT to address this issue. In experiment 1, the solar panel output power graph reached a peak of 862.7 watts but exhibited instability. In contrast, the boost converter output power graph, optimized using the MPPT-PSO algorithm, achieved a maximum power of 736.5 watts with a more stable power fluctuation pattern.